INHIBITION OF STAPHYLOCOCCUS AUREUS STRAINS BY SECONDARY METABOLITES OF STREPTOMYCES SP. (PRÁXIS EM SAÚDE, 2026)
Streptomyces is recognized for its ability to produce bioactive compounds with antimicrobial activity. This study evaluated the activity of metabolites from Streptomyces sp. against clinical strains of Staphylococcus aureus. The extract was obtained by submerged fermentation, followed by antimicrobial activity assays, agar diffusion tests, and determination of the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC). Standard strains ATCC 25923, ATCC 29213, and the clinical strain IC 2141 were tested. The extract showed inhibition zones ranging from 17 ± 0.82 mm to 19.33 ± 1.15 mm. MIC and MBC analyses revealed significant inhibitory and bactericidal activity, with emphasis on strain IC 2141 (MIC and MBC of 625 µg/mL). The results demonstrate that Streptomyces produces metabolites with antibacterial potential, including activity against strains resistant to conventional antibiotics. It is concluded that actinobacteria represent a promising source of bioactive compounds, reinforcing the importance of microbial bioprospecting in the development of therapeutic alternatives.
Keywords: Metabolites; Bacterial Resistance; Bioactive Compounds